2003
DOI: 10.1097/00002826-200309000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Poor Tolerability of a Transdermal Nicotine Treatment in Parkinson's Disease

Abstract: Studies assessing the effect of transdermal nicotine in Parkinson's disease (PD) have generated mixed results regarding its efficacy to treat motor and cognitive deficits. These studies generally reported good tolerability in nonsmoking PD patients. The authors report the tolerability data of an open trial with transdermal nicotine in PD. Twenty-two therapeutically well-controlled nonsmoking PD patients received a transdermal nicotine treatment over 25 days according to the following fixed titration schedule: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…For example, in a trial including 24 nonsmoking PD patients who received a transdermal nicotine treatment over 25 days, 14 participants had side effects such as nausea, vomiting, and dizziness, and 10 of them withdrew from the study [108]. These possible adverse effects highlight the importance of understanding the potential effect of low-dose nicotine obtained from other sources, such as edible solanaceae foods.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a trial including 24 nonsmoking PD patients who received a transdermal nicotine treatment over 25 days, 14 participants had side effects such as nausea, vomiting, and dizziness, and 10 of them withdrew from the study [108]. These possible adverse effects highlight the importance of understanding the potential effect of low-dose nicotine obtained from other sources, such as edible solanaceae foods.…”
Section: Introductionmentioning
confidence: 99%
“…The angular position of both wrists was recorded by means of a diadochokinesimeter (described in Beuter et al, 1999). The reference group (controls) performed four trials whereas the patients performed two trials, because they were tested according to a slightly different protocol (presented in Lemay et al, 2003). Recordings from a healthy control and a patient with PD are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…= 5.98) were non-demented, non-depressive patients with PD, at stages II to III on the Hoehn and Yahr (1967) that participated in an early study (Lemay et al, 2003(Lemay et al, , 2004 and underwent the test in the baseline condition, i.e. under normal medication ( Table 1).…”
Section: Subjectsmentioning
confidence: 99%
“…Their findings suggested that prolonged use of the nicotine patches may result in cerebrovascular disease. Lemay et al [2003] reported complications during repeated-dose nicotine treatment in patients with Parkinson's disease, in which 64% of patients experienced nausea, vomiting, and dizziness after receiving 7 mg nicotine for 11 days, followed by 14 mg for 11 days and then 21 mg for the last 3 days.…”
Section: Nicotinementioning
confidence: 99%